L-Cysteine Desulfhydrase 1 modulates the generation of the signaling molecule sulfide in plant cytosol - Romero, Luis C. (Landes Bioscience, 2013)
Consistent with data in animal systems, experimental evidence highlights sulfide as a signaling molecule of equal importance to NO and H(2)O(2) in plant systems. In mammals, two cytosolic enzymes, cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE), have been shown to be responsible for the endogenous production of sulfide. L-cysteine desulfhydrase 1 (DES1) has been recently established as the only enzyme that is involved in the generation of hydrogen sulfide in plant cytosol. Although plants have an available source of sulfide within chloroplasts, the basic stromal pH prevents sulfide release into the cytosol. Therefore, DES1 is essential for the production of sulfide for signaling purposes.